Acute Cholangitis GRADE II–III. The View of an Interventional Radiologist - O. I. Okhotnikov; M. V. Yakovleva; N. I. Shevchenko; S. N. Grigoriev; O. O. Okhotnikov (Неотложная медицинская помощь, 2024)
Aim of study To evaluate the safety and efficacy of percutaneous transhepatic cholangiostomy (PTC) as a first-line intervention in the treatment of patients with acute cholangitis (AC) Grade II–III (TG 13/18).Material and methods The results of treatment of 42 patients with AC Grade II–III, who underwent PTC, were analyzed. The criteria for non-inclusion were the presence in patients of destructive cholecystitis and (or) acute pancreatitis, AC due to proximal block of the bile ducts, regardless of etiology, as well as the presence of cholangiogenic liver abscesses. Literature data were used as reference results of the use of endoscopic techniques. AC was diagnosed and its severity was determined in accordance with the diagnostic criteria TG 13/18. The control points of the study were the frequency of post-manipulation complications associated with PTC, as well as the immediate efficacy of cholangiostomy, assessed by the dynamics of Grade-status within 24 and 48 hours.Results In all 42 patients, PTC was technically successful. Major complications that might require a change in treatment tactics (significant hemobilia, bile peritonitis, bleeding into the abdominal cavity) were not observed. Two complications occurred: subcapsular hematoma (2.4%) and right-sided pleurisy (2.4%). When assessing the dynamics of Grade status, its significant decrease was found in the group of patients with initial Grade III after 24 hours (from 16 to 9 hours) and 48 hours (from 9 to 4 hours). In patients with initial Grade II status, in three cases it worsened to Grade III, which still persisted in one patient even in 48 hours. There was no in-hospital mortality in the examined patients.Conclusion Antegrade endobiliary intervention for acute cholangitis involves performing real-time monitored biliary decompression. Experience with the use of percutaneous interventions does not confirm the high risk and frequency of post-manipulation complications in comparison with endoscopic retrogradeprocedures. It seems obvious that there is a need for and the possibility of choosing both retrograde and antegrade methods of emergency biliary decompression in the arsenal of treatment for patients with acute cholangitis.